Les mutations de notre économie-monde : Des révolutions sans miracles - Paquet, Gilles (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
This paper attempts to put the present mutation of the world economy in historical perspective. It uses a meso-analytical framework to examine the economic transformation we are experiencing. The main force at work, it is claimed, is a progressive dematerialization of economic activity which has triggered a reorganization of the world economy as instituted process. The extent to which a new international industrial order is in the making is examined together with the forces at work to transform the present conflictive equilibrium situation into a situation of creative disequilibrium.